Impacts of Short-Term Fine Particulate Matter Exposure on Blood Pressure Were Modified by Control Status and Treatment in Hypertensive Patients. Issue 1 (1st June 2021) - Lin, Zhennan; Wang, Xinyan; Liu, Fangchao; Yang, Xueli; Liu, Qiong; Xing, Xiaolong; Cao, Jie; Li, Jianxin; Huang, Keyong; Yan, Weili; Liu, Tingting; Fan, Meng; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Previous studies revealed that fine particulate matter (PM2.5 ) exposure adversely affected blood pressure (BP), but factors that might attenuate this association were still unclear. Using a multicenter panel study among 277 hypertensive participants with intermediate-to-high risk of cardiovascular disease from 4 cities in China, we aimed to explore whether BP control status and antihypertensive medications were potential modifying factors. Each participant carried personal-portable monitors to record individual real-time PM2.5 levels and 24-hour ambulatory BP up to 3× within 1 year. Generalized linear mixed model with individual-specific random intercept was used to assess effect sizes. We identified adverse impacts of short-term PM2.5 exposure on BP. However, these impacts were attenuated among patients with controlled BP. For example, per interquartile range (43.78 µg/m 3 ) increment in the prior 10-hour moving average of PM2.5, systolic BP increased −0.20 (95% CI, −0.57 to 0.18) mm Hg and 0.85 (95% CI, 0.36–1.35) mm Hg among those with controlled and uncontrolled BP, respectively ( P interaction, 0.0009). Furthermore, among those with uncontrolled BP, treatment with angiotensin receptor blocker would potentially lower BP in responses to PM2.5, with systolic BP associated with per interquartile range increment in 10-hour moving average PM2.5 of 0.32 (95% CI, −0.37 to 1.00) mm Hg and 1.53 (95% CI, 0.74–2.33) mm Hg among those taking angiotensin receptor blocker or not, respectively ( P interaction, 0.0229). In conclusion, although PM2.5 exposure would increase BP, keeping well-controlled BP status and using angiotensin receptor blockers might attenuate these adverse impacts, which might provide supporting evidence for guiding hypertensive patients who live in areas with high level of PM2.5 .